Virtual Reality Design of Patient Registration for Medical Record Students: Perancangan Virtual Reality Pendaftaran Pasien Untuk Mahasiswa Rekam Medis - Nugroho, Dwi; Farhan, Ishlah Maulana; Fikriansyah, Roihan Rudi; Hastuti, Febriana; Aisy, Hana Rihadatul; Pradipta, Dimas Andrenawan (Procedia of Engineering and Life Science, 2025)
The use of Virtual Reality (VR) technology in higher education can enhance students’ understanding and practical skills, for patient registration training for Medical Records and Health Information students. This study aims to design and develop Virtual Reality software to improve the efficiency and convenience of the learning process. Using a qualitative research approach with Action Research and purposive sampling techniques, involving 4 students and 1 lecturer, the software development utilized Blender for 3D design and Unity for interactive development, resulting in a realistic and immersive patient registration experience. Integration with Self-Registration Kiosks (APM) and physical facilities such as chairs and air conditioning increased registration efficiency. The results indicate that Virtual Reality is effective in enhancing students’ understanding and skills, although there are challenges such as high costs and significant technical support requirements, necessitating continuous efforts to optimize the use of Virtual Reality in education.